Ganoderma Lucidum Polysaccharide Peptide attenuates post myocardial infarction fibrosis via down-regulating TGF-β1/SMAD and relieving oxidative stress - Jia Meng; Ang Ma; Shun Zhang; Dongmei Lin; Shuqian Lin; Min Li; Hong Zhou; Baoxue Yang (Elsevier, 2022)
The Ganoderma lucidum, a well-known Chinese traditional medicine, has been used to prevent and treat cardiovascular diseases. The purpose of this study was to determine whether Ganoderma lucidum polysaccharide peptide (GLPP) has therapeutic effect on cardiac fibrosis. Using both mouse myocardial infarction (MI) model and primarily cultured cardiac fibroblast model, we found that GLPP (150 mg/kg/day) ameliorated cardiac fibrosis and improved cardiac function following MI. We further revealed that GLPP down regulated the expression of fibronectin, collagen I, collagen III and α-smooth muscle actin in the cardiac tissue, mainly through hindering the over activation of TGF-β/SMAD signaling. On the other hand, GLPP significantly decreased the expression of NADPH oxidase 4 (NOX4), and reduced the MDA, SOD and 8-OHdG in myocardial tissue, suggesting GLPP alleviated cardiac fibrosis partially via relieving oxidative stress. The inhibitory effect of GLPP on TGF-β/SMAD and NOX4-derived ROS signaling pathways was further confirmed in TGF-β or H2O2 stimulated neonatal rat cardiac fibroblast model. Our experimental results indicate that GLPP is a promising agent for the prevention and treatment of cardiac fibrosis.